EFEKTIVITAS MEDIA BONEKA TANGAN DALAM MENINGKATKAN KETERAMPILAN BERBICARA SISWA SEKOLAH DASAR KELAS V SDN INPRES YOTEFA MELALUI CERITA FABEL - Amelia Warikar; Dian Septikasari (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Based on the results of the conducted research, it can be concluded that the use of fable-based hand puppet media has proven effective in improving the speaking skills of elementary school students, particularly fifth-grade students at SDN Inpres Yotefa, Jayapura City. This is evidenced by an increase in the average speaking skill score from 63.2 (pretest) to 81.6 (posttest), as well as the paired t-test results showing a significance value of 0.000 (p < 0.05). Improvement occurred across all assessment aspects, namely fluency, vocabulary, and expression with intonation. The use of hand puppets created an engaging learning environment, enhanced students’ confidence, and encouraged them to express ideas orally more freely in a creative setting. The fable stories used as learning content also contributed to enriching students’ vocabulary and familiarizing them with constructing oral narratives with a clear structure. Thus, hand puppet media serves not only as a visual aid but also as a pedagogical tool capable of fostering active and meaningful learning in the development of elementary school students’ speaking skills.